After neoliberalism the left and economic reforms in Latin America - Flores-Macias, Gustavo (Oxford : Oxford University Press, 2012)
Gusatvo Flores-Macias' book offers a systemic explanation of why the ever-popular left-wing governments in Latin American countries have become extremely radical or moderate once in power.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Latin America -- Economic policy; Neoliberalism -- Latin America; Political parties -- Latin America; Latin America -- Politics and government -- 21st century; Latin America -- Politics and government -- 20th century